AB0440 CHANGES IN KEY LABORATORY VALUES WITH TOFACITINIB 5 MG BID TREATMENT IN PATIENTS WITH PSORIATIC ARTHRITIS AND RHEUMATOID ARTHRITIS. (June 2019) - Rigby, William; Burmester, Gerd Rüdiger; Fitzgerald, Oliver; Azevedo, Valderilio F.; Nash, Peter; Graham, Daniela; Wang, Cunshan; Jones, Thomas
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of psoriatic arthritis (PsA) and rheumatoid arthritis (RA). In most countries where tofacitinib is approved, 5 mg twice daily (BID) is the recommended dose for PsA and RA. An important component of any product labelling is information on the need for laboratory monitoring. Objectives: This post hoc analysis aimed to provide information on the effect of tofacitinib 5 mg BID on laboratory values in PsA and RA patients (pts). Methods: For analysis of pts with active PsA treated with tofacitinib 5 mg BID, data were pooled from 2 Phase 3 studies and an ongoing long-term extension (LTE) study (data cut-off, 25 January 2017; database not locked; data may change). For analysis of pts with moderate or severe RA treated with tofacitinib 5 mg BID, data were pooled from 8 Phase 2, 7 Phase 3, and 1 LTE studies (data cut-off, 2 March 2017; for LTE, database not locked; data may change). All PsA and most RA pts received a background conventional synthetic disease-modifying antirheumatic drug. Data (to Month 12) for pts receiving constant tofacitinib 5 mg BID were evaluated, comprising pts who received tofacitinib 5 mg BID across studies, either at randomisation or following switch from placebo. Pts in the placebo groups who switched to tofacitinib 5 mg BID at Month 3 were included from the time they first received tofacitinib. Pts who switched tofacitinib dose were excluded. Change from baseline in haematologic (haemoglobin, neutrophils, lymphocytes) and lipid (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, total cholesterol, triglyceride) levels and key liver tests (bilirubin, alanine aminotransferase, aspartate aminotransferase) were analysed. Although not addressed in the product labelling, creatine kinase, creatinine and C-reactive protein levels were also assessed. Pts meeting protocol-defined discontinuation criteria for laboratory values were evaluated. Results: The constant tofacitinib 5 mg BID group comprised 348 PsA pts and 3040 RA pts. Mean (standard error) changes/percentage changes from baseline for laboratory values are presented in the table. Laboratory values generally stabilised after 1 to 3 months, and lymphocyte levels stabilised by 24 months (data not shown). In both PsA and RA, ≤3.0% of patients met discontinuation criteria for any laboratory values. Conclusion: In this post hoc analysis of laboratory data with tofacitinib 5 mg BID, changes in key laboratory values were similar for PsA and RA, and discontinuations due to protocol criteria being met for laboratory values were infrequent. These results provide further information on the effect of tofacitinib on laboratory values in PsA and RA. Acknowledgement: This study was sponsored by Pfizer Inc. Medical writing support was provided by Karleen Nicholson, PhD, on behalf of CMC Connect, a division of McCann Health Medical Communications Ltd, Macclesfield, UK, and was funded by Pfizer Inc. Disclosure of Interests: William Rigby Consultant for: Pfizer Inc, Gerd Rüdiger Burmester Consultant for: Roche, Sanofi-Genzyme, Speakers bureau: Roche, Sanofi-Genzyme, Oliver FitzGerald: None declared, Valderilio F Azevedo Grant/research support from: AbbVie, GSK, Janssen, Merck Serono, Novartis, Pfizer Inc, UCB, Consultant for: AbbVie, GSK, Janssen, Merck Serono, Novartis, Pfizer Inc, UCB, Peter Nash Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Daniela Graham Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Cunshan Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Thomas Jones Shareholder of: Pfizer Inc, Employee of: Pfizer Inc